Constitutionalism in an old key: Legality and constituent power - David Dyzenhaus (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
I argue that legal and constitutional theory should avoid the idea of constituent power. It is unhelpful in seeking to understand the authority of law and the place of written constitutions in such an understanding. In particular, it results in a deep ambivalence about whether authority is located within or without the legal order. That ambivalence also manifests itself within positivist legal theory, which explains the affinity between theories of constituent power and legal positivist accounts of authority. Legal theory should then focus on the question of law's authority as one entirely internal to legal order, thus making the question of constituent power superfluous.
Keywords: 320; legal theory; constitutional theory; constituent power; positivist legal theory